1999
DOI: 10.1152/jn.1999.82.2.1074
|View full text |Cite
|
Sign up to set email alerts
|

Fictive Rhythmic Motor Patterns Induced by NMDA in an In Vitro Brain Stem–Spinal Cord Preparation From an Adult Urodele

Abstract: An in vitro brain stem-spinal cord preparation from an adult urodele (Pleurodeles waltl) was developed in which two fictive rhythmic motor patterns were evoked by bath application of N-methyl-D-aspartate (NMDA; 2.5-10 microM) with D-serine (10 microM). Both motor patterns displayed left-right alternation. The first pattern was characterized by cycle periods ranging between 2.4 and 9. 0 s (4.9 +/- 1.2 s, mean +/- SD) and a rostrocaudal propagation of the activity in consecutive ventral roots. The second pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
57
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 9 publications
10
57
0
Order By: Relevance
“…The CPG underlying axial motion-the body CPG-is located all along the spinal cord. Similarly to the lamprey (Cohen and Wallen, 1980), it spontaneously propagates traveling waves corresponding to fictive swimming when induced by NMDA excitatory baths in isolated spinal cord preparations (Delvolvé et al, 1999). Small isolated parts of two to three segments can be made to oscillate suggesting that rhythmogenesis , 1997.…”
Section: Related Work Neural Control Of Salamander Locomotionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CPG underlying axial motion-the body CPG-is located all along the spinal cord. Similarly to the lamprey (Cohen and Wallen, 1980), it spontaneously propagates traveling waves corresponding to fictive swimming when induced by NMDA excitatory baths in isolated spinal cord preparations (Delvolvé et al, 1999). Small isolated parts of two to three segments can be made to oscillate suggesting that rhythmogenesis , 1997.…”
Section: Related Work Neural Control Of Salamander Locomotionmentioning
confidence: 99%
“…Locomotion of the salamander is controlled by a central pattern generator (CPG), i.e., a network of neurons capable of producing coordinated patterns of rhythmic neural activity without rhythmic inputs (Delvolvé et al, 1999). The CPG underlying axial motion-the body CPG-is located all along the spinal cord.…”
Section: Related Work Neural Control Of Salamander Locomotionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if, in the initial experiments, the transection of the dorsal roots does not exclude the influence of sensory feedback as pointed out by Grillner and Zangger (1984), there is now very clear evidence that rhythms can be generated centrally without requiring sensory information. Indeed, experiments on lampreys (Cohen and Wallen (1980), Grillner (1985)), on salamanders (Delvolvé et al (1999)) and on frog embryos (Soffe and Roberts (1982)) have shown that when the spinal cord is isolated from the body, electrical or chemical stimulations activate patterns of activity, called fictive locomotion, very similar to the ones observed during intact locomotion. Since then, the CPGs hypothesis has been strengthen by experiments on both vertebrates and invertebrates (see Stein et al (1997) or Ijspeert (2008) for more comprehensive reviews).…”
Section: Central Pattern Generatorsmentioning
confidence: 98%
“…As we find in postmetamorphic Xenopus, NA modulates ongoing locomotor rhythmicity in the spinal cat (Rossignol et al, 1998) and the isolated neonatal rat spinal cord (Kiehn et al, 1999) by increasing both motor cycle periods and burst durations. However, it must be emphasized that our Xenopus experiments on spontaneously expressed patterns of fictive swimming differed fundamentally from most other vertebrate studies in which extant locomotor activity required sensory (e.g., via treadmill walking) or supraspinal stimulation in vivo (Steeves et al, 1980), or additional neurochemical stimulation in vitro (Grillner, 1986;Cazalets et al, 1992;Jovanovic et al, 1996;Delvolve et al, 1999;Jiang et al, 1999). Thus, distinguishing aminespecific actions from a combination of inductive/modulatory processes becomes problematic.…”
mentioning
confidence: 93%